1989
DOI: 10.1016/s0006-3495(89)82875-9
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning and location of Bay K 8644, 1,4-dihydropyridine calcium channel agonist, in model and biological membranes

Abstract: Several lines of evidence suggest that nonspecific drug interaction with the lipid bilayer plays an important role in subsequent recognition and binding to specific receptor sites in the membrane. The interaction of Bay K 8644, a 1,4-dihydropyridine (DHP) calcium channel agonist, with model and biological membranes was examined at the molecular level using small angle x-ray diffraction. Nonspecific drug partitioning into the membrane was examined by radiochemical assay. Nonspecific binding characteristics of [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…X-ray diffraction experiments were conducted by aligning the samples at grazing incidence with respect to a collimated x-ray source (CuK␣ radiation; ϭ 1.54 Å). In addition to direct calibration of the detector system, cholesterol monohydrate crystals were used to verify the calibration, sample-to-detector distance, and location of the main beam, as described previously (26). The unit cell periodicity (d-space) of the membrane lipid bilayer was calculated using Bragg's law.…”
Section: Preparation Of Oriented Membranes For Smallmentioning
confidence: 99%
See 1 more Smart Citation
“…X-ray diffraction experiments were conducted by aligning the samples at grazing incidence with respect to a collimated x-ray source (CuK␣ radiation; ϭ 1.54 Å). In addition to direct calibration of the detector system, cholesterol monohydrate crystals were used to verify the calibration, sample-to-detector distance, and location of the main beam, as described previously (26). The unit cell periodicity (d-space) of the membrane lipid bilayer was calculated using Bragg's law.…”
Section: Preparation Of Oriented Membranes For Smallmentioning
confidence: 99%
“…Corrected diffraction orders obtained from samples in this study were analyzed using Fourier summation to yield one-dimensional electron density profiles (Å versus electrons/Å 3 ) of the membrane lipid bilayer. A detailed explanation of membrane diffraction analysis was described previously (26).…”
Section: Preparation Of Oriented Membranes For Smallmentioning
confidence: 99%
“…The primary reason for a centrosymmetric structure is that the stacking of the membranes results in a random orientation for the SPM with respect to the multilayer direction. The SPM electron density profiles were normalized to the phospholipid headgroup region, a region of relatively high electron density, after applying identical correction factors to the raw diffraction data (28,29).…”
Section: Sds-polyacrylamide Gel Electrophoresis Of A␤ 1-40 -mentioning
confidence: 99%
“…This finding suggests that A␤ modulates membrane function by a nonreceptor-mediated mechanism, potentially as a result of altering the physico-chemical properties of membrane constituents, including lipids and proteins (13)(14)(15)(16). Indeed, previous membrane equilibrium binding experiments have demonstrated that the A␤ [25][26][27][28][29][30][31][32][33][34][35] fragment is highly lipophilic (K P Ͼ 10 2 ); the peptide intercalates deep into the membrane bilayer hydrocarbon core, as determined by small angle x-ray diffraction approaches (15). In addition, aggregated A␤ has strong electrostatic interactions with the surface of model membranes that appear to mediate its neurotoxicity (17).…”
mentioning
confidence: 95%
See 1 more Smart Citation